2019
DOI: 10.18502/ijps.v14i3.1321
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bad News: A Valid Concern among Clinicians

Abstract: Objective: Delivering bad news is the duty of specialist physicians. However, they find it very difficult due to insufficient experience. In this study, the way faculty and residents of Guilan University of Medical Sciences (GUMS) delivered bad news to the patients was investigated. Method: This study was conducted at hospitals affiliated to GUMS during 2017. A questionnaire containing 18 items on environmental and psychical support was filled through a face to face interview. The first 10 questions evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
2
16
0
1
Order By: Relevance
“…Also, it developed a greater capacity for treating others with respecting and understanding of requirements in palliative care nursing (20). Moreover, similar to Biazar et al (16), we found that age and years of experience were positively correlated with higher scores. Overall, these results show that therapeutic teams, including physicians and nurses, should act better based on their experience, not according to educational programs, a thought-provoking finding that needs special attention.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, it developed a greater capacity for treating others with respecting and understanding of requirements in palliative care nursing (20). Moreover, similar to Biazar et al (16), we found that age and years of experience were positively correlated with higher scores. Overall, these results show that therapeutic teams, including physicians and nurses, should act better based on their experience, not according to educational programs, a thought-provoking finding that needs special attention.…”
Section: Discussionsupporting
confidence: 86%
“…Biazar et al found that only 19.1% of faculty members and residents of GUMS had the belief that it is the patients' right to know about their exact survival time. In this study, this belief was even less probable, and only 17.7% of the nurses had the perspective of being honest about this topic (16).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It has been shown that patients' preferences on the way to break bad news vary from those of the physicians ( 3 ). Patients prefer to obtain clear information about the progression and prognosis of disease, as well as about anticipated life expectancy, while in practice this information are not easily provided in clear terms.…”
Section: Introductionmentioning
confidence: 99%
“…Ocorre que, por sua natureza relacional, a comunicação de más notícias não pode ser reduzida a um procedimento fundamentado em um único saber especializado, conforme adverte Krieger (2017). Na rotina de hospitais brasileiros, todavia, comumente médicos são os únicos responsáveis por tal atividade, embora não se sintam capacitados para tanto por compreenderem que não conseguem responder adequadamente às questões emocionais suscitadas pela ação comunicacional (Biazar et al, 2019;Vogel et al, 2019;Monteiro & Quintana, 2016).…”
Section: Introductionunclassified